Monitoring and Controlling Electric Energy Usage Based on the Internet of Things - Abdul Latif, Luthfi; Hambali; Maulana, Ricky; Hidayat, Rahmat (Journal of Industrial Automation and Electrical Engineering, 2024)
Electrical energy is one of the basic human needs whose use continues to increase along with the increase in daily activities. Uncontrolled electricity consumption can lead to energy waste and increased costs. Therefore, a system is needed that can monitor and control the use of electrical energy effectively. In this final project, we develop an Internet of Things (IoT)-based tool that is able to monitor and control the use of household electrical energy in real-time. This system uses ESP32 microcontroller, PZEM-004T current sensor, LCD to display the sensor output, and Relay as an automatic switch to regulate the on or off of electronic devices. Blynk platform is used as an intermediary between microcontroller and smartphone or PC to facilitate remote control. With this system, users can monitor daily energy consumption and control electricity usage efficiently, thus saving energy and costs. This research is expected to contribute to a smarter and more efficient management of household electrical energy